SELF-DIRECTED LEARNING IN EFL DURING COVID-19 PANDEMIC: AN ANALYSIS OF TEACHER’S PERCEPTIONS AND STUDENTS’ LEARNING AUTONOMY IN SMA N 2 AMLAPURA - Setiawan, I Made Hardi (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
This study aims to analyze English teacher’s perceptions of Self-directed learning, describe the activities assigned by the teacher in online learning, and identify the Self-directed learning component that can be identified in the online learning activities. Qualitative and quantitative methods are used in this study. The teacher claims herself knowledgeable about Self-directed learning, often implement SDL, and claims SDL has a very influential impact on the students. The teacher is still difficult to handle online learning, especially in pre-activity and post-activity. There is a discrepancy appeared in this study between teacher’s perceptions and the action in reality. From seven indicators, the teacher only can implement two indicators. There is an indication the implementation of Self-directed learning in online learning is not effective yet.Keywords: Self-directed learning, Teacher’s perception, Learning autonomy, Online learning.